Glycopyrronium for chronic obstructive pulmonary disease: evidence and rationale for use from the GLOW trials. (December 2014) - Miravitlles, Marc; Beeh, Kai-Michael; Altman, Pablo
The clinical development of the long-acting muscarinic antagonist bronchodilator glycopyrronium (Seebri ® Breezhaler ® inhalation powder) in the GLOW (glycopyrronium bromide in chronic obstructive pulmonary disease airways) series of studies showed that, compared with placebo, once-daily glycopyrronium provided 24-h bronchodilation, improved symptoms and health status and reduced the risk and rate of moderate or severe exacerbations. Glycopyrronium also reduced dynamic hyperinflation and increased exercise tolerance. Compared with the long-acting muscarinic antagonist tiotropium, glycopyrronium had a similar effect on clinical outcomes with a faster onset of action. Added to the long-acting β2 -agonist bronchodilator indacaterol, glycopyrronium had a greater bronchodilator effect and improved dyspnea versus indacaterol alone. There were no significant safety issues in the GLOW studies. Glycopyrronium is a useful addition to the treatments for chronic obstructive pulmonary disease.